2011
DOI: 10.1167/iovs.10-5944
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Antiviral Efficacy of an Ophthalmic Formulation of Dexamethasone Povidone-Iodine in a Rabbit Model of Adenoviral Keratoconjunctivitis

Abstract: FST-100 was the most efficacious in minimizing the clinical symptoms of adenovirus infection in rabbit eyes. FST-100 and 0.5% cidofovir were both equally effective in reducing viral titers and decreasing the duration of viral shedding. By providing symptomatic relief in addition to reducing infectious virus titers, FST-100 should be a valuable addition to treatment of epidemic adenoviral keratoconjunctivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 42 publications
1
53
0
Order By: Relevance
“…This small, open-label human clinical trial was conducted in light of the extensive ophthalmic use of these two drugs: povidone-iodine [19][20][21][22][23][24][25][26] and dexamethasone. 10,[16][17][18] After the study by Pelletier et al 16 was published, Clement et al 29 published results on tests on rabbit corneas and showed that povidone-iodine 0.4% dexamethasone 0.1% was the most effective agent in minimizing the clinical signs of adenovirus infection in rabbit eyes when the treatment was compared to cidofovir 0.5%, tobramycin/dexamethasone ophthalmic suspension and balanced salt solution. The study concludes with a request for a human phase III clinical trial to test the efficacy of this drug on a larger group and also to evaluate the safety of the treatment in order to properly establish both the therapeutic benefit and any negative side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This small, open-label human clinical trial was conducted in light of the extensive ophthalmic use of these two drugs: povidone-iodine [19][20][21][22][23][24][25][26] and dexamethasone. 10,[16][17][18] After the study by Pelletier et al 16 was published, Clement et al 29 published results on tests on rabbit corneas and showed that povidone-iodine 0.4% dexamethasone 0.1% was the most effective agent in minimizing the clinical signs of adenovirus infection in rabbit eyes when the treatment was compared to cidofovir 0.5%, tobramycin/dexamethasone ophthalmic suspension and balanced salt solution. The study concludes with a request for a human phase III clinical trial to test the efficacy of this drug on a larger group and also to evaluate the safety of the treatment in order to properly establish both the therapeutic benefit and any negative side effects.…”
Section: Discussionmentioning
confidence: 99%
“…16 In another study, dexamethasone 0.1%/povidone-iodine 0.4% combination markedly lowered the viral concentration and improved the signs of the disease in rabbits. 29 Thus, favorable human data in combination with in vivo results provide an impetus for a human clinical trial to test the efficacy of this drug on a larger group and to evaluate the safety of the treatment in order to properly establish both the therapeutic benefits and the adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…37 The authors of another study confirmed ''the efficacy of topical dexamethasone 0.1%/povidone-iodine 0.4% (FST-100) in reducing clinical symptoms and infectious viral titers in a rabbit model of adenoviral keratoconjunctivitis.'' 38 This study concluded that FST-100 has the potential to become the preferred drug in treating adenoviral conjunctivitis in humans and could be most effective in the treatment of more serious forms of infection, including EKC. 38 Reports of off-label use of povidone-iodine have also claimed to preserve visual function and reduce viral spread.…”
Section: Introductionmentioning
confidence: 88%
“…38 This study concluded that FST-100 has the potential to become the preferred drug in treating adenoviral conjunctivitis in humans and could be most effective in the treatment of more serious forms of infection, including EKC. 38 Reports of off-label use of povidone-iodine have also claimed to preserve visual function and reduce viral spread. 39 One protocol calls for the medical provider to anesthetize the affected eye, instill a pretreatment NSAID, then instill four to five drops of 5% povidone-iodine solution, have the patient roll his or her eyes around for full exposure, swab the lid margins with the solution while the patient waits for approximately 60 s and finally lavage the ocular tissue with sterile saline irrigating solution.…”
Section: Introductionmentioning
confidence: 88%
“…It was reported that povidone iodine reduced viral load and the severity of symptoms in vitro and in vivo studies for the treatment of epidemic keratoconjunctivitis. 17,18 However, there are no controlled trials supporting the use of this non-specific treatment option.…”
Section: Introductionmentioning
confidence: 99%